Withdrawal of ventilatory support outside the intensive care unit. (24th May 2012) - Laddie, JRL; Craig, F; Brierley, J
Abstract : Aims: Withdrawal of invasive organ support, if aggressive treatment is no longer in a child's best interests, traditionally occurs within intensive care units (ICU). Sporadic reports of transfer outside ICU for withdrawal exist with evidence suggesting many families would prefer their dying child to go home, and in this context choice in place of care, and subsequently of death, should be offered. Our hospital is a tertiary paediatric hospital with children from throughout the UK, meaning such discharges present specific challenges with practical, logistical and legal considerations that must be addressed. Methods: Retrospective eight-years (2003-2011) case-note (ICU and palliative care notes) review of transferring children out of ICU for withdrawal of ventilatory support. Common themes and specific incidents were identified in order to develop local guidelines for transfer and subsequent management. Results: 13 children were considered, but 3 died prior to transfer organisation. Of those transferred 4 went home, 4 to hospices, 1 to another hospital ward and 1 to a residential school. Ages ranged from 1-month to 16 years. There were a variety of primary pathologies (malignant, neurological, renal and respiratory diseases). Formal multidisciplinary team meetings prior to discharge were recorded in only 5 cases prior to transfer, and community team involvement was not documented at this stage in any case. 6 children had Symptom Management Plans and 1 an emergency care plan in event of longer than anticipated survival. No documented fluid management plan for longer-term survival was found in any case, though these existed, and 1 transfer occurred without discharge medications. Concerns raised included: transfer timings, health professionals availability to manage transfer and withdrawal, access to properties, availability of support in the community, symptom management post ventilation withdrawal and drug administration. Legal concerns included death certification, cremation form completion and the transfer of coronial jurisdiction and National legal administration. Conclusion: Although National guidance has recently been published, we have developed local guidelines based on our own experience as specific considerations occur dealing with teams from different regions. This is especially challenging when transfer must be arranged rapidly. Specific documentation is now mandatory.